Open Cell Aluminum Foams Produced by Polymer Impregnation Method - Zaman, E.; Keleş, Ö. (Institute of Physics, Polish Academy of Sciences, 2014)
In this study, open cell aluminum foams were produced using the polymer impregnating method. This method consists of slurry preparation, template coating, drying, burning and nally sintering. Physical properties of the open cell aluminum foams were characterized. Microstructures were investigated utilizing optical and scanning electron microscopy. Cu Kα was used as X-ray source in phase analysis. The hardness of the foams was measured by applying Vickers hardness test. An ideal foam coating was achieved using the slurry having 60% solid content mixed with a speed of 1000 rpm for 3 h. The polyurethane foam was burned out at 500 ◦C and ideal sintering parameters were 620 ◦C for 4 or 7 h. The foam densities containing 60% solid were found to be 0.12 0.15 g/cm. The porosity values were calculated to be in the range of 94.4 95.5%. Micro hardness values were 30.3 34.7 Hv.